Politik Hukum Pidana Terhadap Penanggulangan Kejahatan Illegal Logging - Satria Bimantara Burhan; Wahyu Prawesthi; Bachrul Amiq (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The results of the study are as follows: the application of current criminal sanctions against perpetrators of illegal logging in the forestry sector, hereinafter known as illegal logging, is imposed as formulated in Article 78 regarding criminal provisions. The sanctions imposed are: 1). imprisonment 2) Fine 3). confiscation of all forest products and tools used for crimes or violations. This shows that the criminal threat in this crime belongs to the severe category, in its application this article is generally applied indiscriminately, to the perpetrators of the crime of illegal logging who utilize forest products just to cover economic needs with the perpetrators of the cukong, as well as the owners. capital and who actually take large profits from the use of forest products without permission from the competent authorities. The philosophy underlying the intent and purpose of imposing severe criminal sanctions on anyone who violates the law in the forestry sector is to create a deterrent effect for violators of the law in the forestry sector. The intended deterrent effect is not only for perpetrators who have committed forestry crimes, but also for other people who have activities in the forestry sector who are reluctant to commit acts that violate the law because the criminal sanctions are severe.